Control of campylobacter in poultry industry from farm to poultry processing unit: A review. Issue 4 (4th March 2017) - Umaraw, Pramila; Prajapati, A.; Verma, Akhilesh K.; Pathak, V.; Singh, V. P.
ABSTRACT: Campylobacter is an emerging zoonotic bacterial threat in the poultry industry. Most of the human cases of campylobacteriosis recorded have revealed their poultry origins. Various control measures have been employed both at the farm and processing levels to combat with it. The antibiotic treatment, phage therapy, competitive exclusion, and vaccination have been adapted at the farm level to reduce colonization of Campylobacter in poultry gut. While prevention of intestinal spillage, scheduled slaughter, logistic slaughter, chemical decontamination of carcasses are recommended to reduce contamination during processing. The postharvest interventions such as heat treatment, freezing, irradiation of contaminated carcass can effectively reduce Campylobacter contamination. Thus, integrated approaches are required to tackle infection of Campylobacter in humans.